On the Optimality of the Stock Market Allocation of Investment - Stiglitz, J. E. (Quarterly Journal of Economics, 1972)
I. Introduction, 25.–II. The basic model, 27.–III. Determination of the level of investment in a mean variance model, 32.–IV. Choice of technique, 47.–V. Remarks on alternative models of market equilibrium, 52.–VI. Concluding remarks, 55.–Appendix, 57.